2011
DOI: 10.1111/j.1463-1326.2011.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 11β-hydroxysteroid dehydrogenase type 1 inhibitor, MK-0916, in patients with type 2 diabetes mellitus and metabolic syndrome

Abstract: Inhibition of HSD1 with MK-0916 was generally well tolerated in patients with T2DM and MetS. Although no significant improvement in FPG was observed with MK-0916 compared to placebo, modest improvements in A1C, body weight and blood pressure were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 20 publications
12
161
2
4
Order By: Relevance
“…An additional study has also demonstrated increased 5bR activity with increasing hepatic fat (78). Although selective 11b-HSD1 inhibitors have not been studied in the context of hepatic steatosis, in patients with diabetes, they caused modest improvement in glycaemic control and weight loss and improved lipid profiles (79,80).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…An additional study has also demonstrated increased 5bR activity with increasing hepatic fat (78). Although selective 11b-HSD1 inhibitors have not been studied in the context of hepatic steatosis, in patients with diabetes, they caused modest improvement in glycaemic control and weight loss and improved lipid profiles (79,80).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…There were also reductions in weight (−1.8 kg) and blood pressure (systolic −7.9 mmHg and diastolic −5.4 mmHg). In patients without statin treatment, MK-0916 increased total cholesterol and LDL-cholesterol by about 10% [89]. In similarly overweight/obese volunteers with metformin-treated type 2 diabetes, 200 mg daily of INCB-13739 for 12 weeks lowered HbA 1c (−0.6%), FPG (−0.64 mmol/l), HOMA-IR (−24%), body weight (≈ −1 kg) and total cholesterol (−3%).…”
Section: βHsd1 Inhibitorsmentioning
confidence: 99%
“…This requires careful consideration and more data even though no serious adverse events have been reported in short-term (3 month) clinical trials published to date [88][89][90][91].…”
Section: Outstanding Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A plazmaglükózértékben nem volt szignifi káns különbség a gyógyszert és a placebót szedők között, de a hypertonia előfordulása, a HbA 1c és a testsúly szignifi kánsan csök-kent a gyógyszert szedők körében [47].…”
Section: Klinikai Vizsgálatokban Kipróbált 11-β-hsd-1-gátlókunclassified